Hydroacoustic, Seismic, and Bathymetric Observations of the 2014 Submarine Eruption at Ahyi Seamount, Mariana Arc. (26th July 2019) - Tepp, Gabrielle; Chadwick, William W.; Haney, Matthew M.; Lyons, John J.; Dziak, Robert P.; Merle, Susan G.; Butterfield, David A.; Young, Charles W.
Abstract: Ahyi seamount, a shallow submarine volcano in the Northern Mariana Islands, began erupting on 23 April 2014. Hydroacoustic eruption signals were observed on the regional Mariana seismic network and on distant hydrophones, and National Oceanic and Atmospheric Administration (NOAA) scuba divers working in the area soon after the eruption began heard and felt underwater explosion sounds. The NOAA crew observed yellow‐orange bubble mats along the shore of neighboring Farallon de Pájaros Island, but no other surface manifestations of the eruption were reported by the crew or observed in satellite data. Here, we detail the eruption chronology and its morphologic impacts through analysis of seismic and hydroacoustic recordings and repeat bathymetric mapping. Throughout the 2‐week‐long eruption, Ahyi produced several thousand short, impulsive hydroacoustic signals that we interpret as underwater explosions as well as tremor near the beginning and end of the sequence. The initial tremor, which occurred for 2 hr, is interpreted as small phreatomagmatic explosions. This tremor was followed by a 90‐min pause before the characteristic impulsive signals began. Occasional tremor (lasting up to a few minutes) during the last 1.5 days of the eruption is interpreted as more sustained eruptive activity. Bathymetric changes show that a new crater, about 150 m deep, formed near the former summit and a large landslide chute formed on the southeastern flank. Comparing to other geophysically detected submarine eruptions, we find that the signals from the 2014 Ahyi eruption were more similar to those from other shallow or at‐surface submarine eruptions than those at deep (>500 m) eruptions. Plain Language Summary: Ahyi seamount, a shallow submarine volcano in the Commonwealth of the Northern Mariana Islands (CNMI), began erupting on 23 April 2014. The U.S. Geological Survey first noticed signs of the eruption during a routine data check on 24 April, while National Oceanic and Atmospheric Administration scuba divers working in the area heard and felt underwater explosion sounds. We analyze recordings of the eruption on the CNMI seismic network and on hydrophones located near Wake Island to detail how the eruption unfolded. The eruption started with about 2 hr of tremor from magma explosively interacting with water. After a 90‐min pause, short (up to a few seconds) explosions began and continued for 2 weeks. During the last 1.5 days of the eruption, longer tremor signals (up to a few minutes) from more sustained degassing eruptions occurred along with the short explosions. A comparison of bathymetric maps made before and after the eruption shows that the explosions formed a new crater 150 m deep near the summit and that a landslide chute formed on the southeastern flank. The seismic and hydroacoustic signals from the Ahyi eruption are more similar to those from eruptions at other shallow or at‐surface seamounts than to those from deep (>500 m) eruptions. Key Points: The submarine volcano Ahyi erupted for 2 weeks in April–May 2014 and was recorded by regional seismometers and distant hydrophones The eruption was characterized by several thousand explosions and occasional tremor at the beginning and end of the eruptive period Repeat bathymetry reveals a new summit crater and a new, large landslide chute on the south flank